Refusals to Invitations Performed by Javanese College Leaners of English in Surakarta by Using Gender as Social Variable - Kuncoro DSM, Sri (2011)
This is a case study of pragmatic which investigates the types of refusal to invitations and their semantic formulas, and the ways of the Javanese college learners of EFL perform the refusal types and their semantic formulas. For this study, 60 Javanese college learners of EFL (30 male and 30 females) are asked to respond in English for ten various situations of invitations in which they carry out the speech act of refusal. The data, collected from Discourse Completion Task (DCT), are analyzed in terms of refusal types, semantic formulas, and the ways of the refusal types and semantic formulas performed by the respondents. The analyzed data basically uses the taxonomy of refusals by Beebe,et.al. (1990), but in this current study the writer uses the modification of taxonomy of refusals from Yamagashira (2001), Wannaruk (2005), and Al Eryani (2007) are chosen. The result of investigation is 600 responses of refusal to invitations. Then, the English performance of the male and female respondents is compared to know the differences and similarities in refusals to invitations. The difference of performing the refusal utterances between the male and the females particularly happen in the frequency of using the refusal utterance not in the forms of refusal utterance, and generally the difference is not significant. The slight difference also happens in the ways of using the refusal utterances to invitations. These facts affirm that language used by the males and the female are different. The refusal utterances to invitations performed by the male and female respondents in the current study are also compared to the refusal utterances to invitations used by American native speakers in the previous studies of Wannaruk (2005) and Al Eryani (2007). From those comparisons between the respondents as non native speakers, and the Americans as native speakers can be revealed that the cultural issues or values underlie the differences, and it causes a pragmatic transfer. The findings advocate implications for EFL teaching methodology, including material and curriculum development, it also confirms that language and culture is inseparable. Furthermore, this study is helpful to understand speech acts and or oral communication across culture.